2021
DOI: 10.3389/fnut.2021.692673
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features and Digestibility of Corn Starch With Different Amylose Content

Abstract: In this study, the in vitro digestibility of corn starch with different amylose content was determined. The results showed that waxy corn starch (WCS) and corn starch (CS) have the highest digestibility, while high amylose corn starch (HACS) has a higher content of resistant starch (RS). Besides being related to amylose content, RS content is also closely related to particle shape, debranched fine structure, molecular structure, and semi-crystalline structure. HACS can maintain a complete particle structure af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…Ruminants possess a better potential to degrade large quantities of starch, which has a different degree of resistance to degradation. Several factors determine the rate and extent of starch digestion in the rumen, such as crystallinity, a ratio of amylose/amylopectin, particle size, and cooking approach ( 1 , 2 ). Amylose and amylopectin are the main components of starch and can determine the nutritional and biochemical properties of starch ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruminants possess a better potential to degrade large quantities of starch, which has a different degree of resistance to degradation. Several factors determine the rate and extent of starch digestion in the rumen, such as crystallinity, a ratio of amylose/amylopectin, particle size, and cooking approach ( 1 , 2 ). Amylose and amylopectin are the main components of starch and can determine the nutritional and biochemical properties of starch ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors determine the rate and extent of starch digestion in the rumen, such as crystallinity, a ratio of amylose/amylopectin, particle size, and cooking approach ( 1 , 2 ). Amylose and amylopectin are the main components of starch and can determine the nutritional and biochemical properties of starch ( 1 ). Amylopectin is a highly branched glucose polymer with α−1, 6-glucoside bonds and has a higher rate of digestion than amylose ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, considering that there were generally no significant differences between groups in the phenotypic outcomes of interest, results from additional assays on these genes are not expected to cause a material difference in the conclusions. Second, the 10% kcal group consumed a diet with some sugar replaced by cornstarch and maltodextrin, which is rapidly absorbed in the small intestine ( 49 ). Although it has been shown that long-term intake of maltodextrin and cornstarch may have adverse health effects such as impaired insulin sensitivity and hyperlipidemia ( 50 ), the difference in % kcal of glucose from digestion of cornstarch and maltodextrin between 10 and 25% kcal sucrose diets in our study is considered small (e.g., 55 vs. 47.5% kcal glucose for 10% and 25% kcal sucrose diets, respectively, assuming 60% kcal from carbohydrates), that would only have minute influences if any on our study results, which overall also showed no significant differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is the primary energy source for the human body and is widely utilized in food production. Native corn starch (NCS) has been used in many food products even though it commonly presents very rapid digestibility [2] because it contains a large amount of rapidly digestible starch (RDS), which might promote some health problems such as type-2 diabetes obesity, and excess weight due to an abrupt rise in glycemic response. [3] Encapsulation of starch granules has been noticeable for slowing down starch hydrolysis because the starch becomes less accessible when surrounded by a food matrix, known as Type 1 resistant starch (RS1).…”
Section: Introductionmentioning
confidence: 99%